PENGARUH PENAMBAHAN EKSTRAK DAUN MANGGA MANALAGI TERHADAP MUTU FISIK DAN EFEKTIVITAS TABIR SURYA EMULGEL KOMBINASI OCTINOXATE-AVOBENZONE - Viddy Agustian Rosyidi; Dwi Nurahmanto; Yudi Wicaksono; Lita Putri Ayu Lestari; Lidya Ameliana (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Avobenzone and octinoxate are often used as a combination of organic UV filters in sunscreen. At high exposure to UV light, these UV filters can be degraded so that their sunscreen’s effectiveness is reduced. Several studies reported that the combination of plant extracts with synthetic UV filters could increase sunscreen's SPF. Mango leaves contain high levels of flavonoids and in several studies have been shown to have photoprotective activity with good Sun Protection Factor (SPF) values. The Manalagi mango plant is a type of mango that is widely planted in yards, so it's easy to get the raw materials. This study aims to determine the effect of manalagi mango leaf extract with a concentration of 1, 3, and 5% on the physical quality (pH, viscosity, spreadability) and sunscreen activity (SPF, %TE, %TP) of sunscreen emulgel containing avobenzone and octinoxate. This study showes that increasing the concentration of manalagi mango leaf extract reduced the pH and viscosity of the preparation, and significantly increased the spreadability of all formulas. Besides that, it can also increase the SPF value and decrease the %TE and %TP values. The emulgel formula that had the highest sunscreen activity was F3 with an extract concentration of 5%, had an SPF value of 30.597 ± 0.600, %TE 0.0001 ± 0.0001, and %TP 0.0038 ± 0.0016.